Role of Self-Control and Self-Construal in the Army Morale and Suicidal Ideation of Chinese Military Cadets - Chen, Outong; Liu, Ranran; Zhao, Xiaojing (Frontiers in Psychology, 2022)
The current study investigated the relationship between army morale and suicidal ideation in Chinese military cadets, including the mediating role of self-control and the moderating role of self-construal. A total of 1124 male navy cadets participated in the study, completing a series of questionnaires. The results revealed the following: (1) army morale could negatively predict suicidal ideation; (2) the negative predictive effect of army morale on suicidal ideation could be partially mediated by self-control; and (3) self-construal moderated the predictive effect of army morale on suicidal ideation among navy cadets. Finally, the current study suggested that building some relevant assessment, diagnostic, and training programs may help build army morale and further prevent suicidal ideation in the military context.